Effect of woven structure and aramid binder yarn on the flexural performance of carbon/aramid fiber hybrid three‐dimensional woven composites. Issue 12 (28th September 2022) - Liu, Yajun; Natsuki, Toshiaki; Huang, Canyi; Nakajima, Takashi; Xia, Hong; Ni, Qing‐Qing
Abstract: Three‐dimensional (3D) woven textile‐reinforced composites have drawn much attention because of their specific geometries, improved composite interlayer strength, and impact‐resistance performance. In this study, three types of 3D woven structures with different binder‐yarn ratios and paths were designed based on a traditional dobby‐weaving loom with a special weft‐interlock structural design. Carbon/aramid fiber‐reinforced plastic (CAFRP) composites with carbon warp, weft, and aramid binder yarns, as well as carbon fiber‐reinforced plastic (CFRP) composites were reinforced using the three types of woven structures and consolidated with epoxy resin. The quasi‐static and dynamic flexural performance of these 3D woven composites were experimentally investigated using a three‐point bending test and a low‐velocity drop‐weight impact test. Nondestructive ultrasonic C‐scan and X‐ray microcomputed tomography were applied to characterize the failure mode of the impacted composites. Woven structure and aramid binder yarn with a coarse count have a coupling effect on the quasi‐static flexural performance of the 3D woven CAFRP composites. A larger volume combined with a smaller through‐thickness waviness degree of aramid binder yarn has a similar effect with a smaller volume combined with a larger waviness degree. Introducing aramid binder yarn in the hybrid composites lowered the quasi‐static flexural performance to a certain extent (0.28%–47.74% and 5.29%–49.63% for flexural modulus and strength, respectively) but increased the impact performance significantly (e.g., increasing 23.6%–92.7% peak‐load values under 6‐J impacts). A larger volume combined with a smaller waviness degree of the aramid binder yarn introduced in these woven structures contributed more to impact‐resistance and damage‐tolerance performance. Abstract : Significantly improved impact performance for 3D woven hybrid carbon/aramid fiber‐reinforced plastic composites with aramid binder yarn compared to their carbon fiber‐reinforced plastic counterparts.